Evaluating Artificial-Intelligence Translation Tools’ Ability to Imitate Human Translators in Translating Synonymous Words in Specialized Texts: تقييم قدْرَة أدوات الترجمة بالذكاء الاصطناعي على محاكاة المترجم البشري في ترجمة المترادفات في النصوص المتخصصة - LAABED, Omar; BADI, Nadjat (Maalim, 2026)
In a world of a fast-paced technological development, the idea that Artificial-Intelligence translation tools can imitate human translators in the English-Arabic language combination may still seem not thoroughly covered. This suggests that there are some aspects that still need more testing and evaluation. This paper aims at evaluating two AI translation tools’ ability to imitate human translators in translating synonymous words from English into Arabic in specialized texts. Using content analysis as the primary research tool, the results showed that the ability of AI translation tools to imitate human translators is limited to the choice of the translation procedures, and that machine-translation post-editing is necessary to validate AI outputted translations.